2020
DOI: 10.3390/ijms21228833
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MicroRNA-1-FAM83A Axis Dysfunction in the Growth and Motility of Lung Cancer Cells

Abstract: Lung cancer is the most prevalent types of cancer and the leading cause of cancer-related deaths worldwide. Among all cancers, lung cancer has the highest incidence, accompanied by a high mortality rate at the advanced stage. Favorable prognostic biomarkers can effectively increase the survival rate in lung cancer. Our results revealed FAM83A (Family with sequence similarity 83, member A) overexpression in lung cancer tissues compared with adjacent normal tissues. Furthermore, high FAM83A expression was closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…MiR-1-3p, a downstream target of NEAT1, has been shown to play a facilitative role in tumors. For instance, Peng et al [ 57 ] reported that miR-1-3p affects gastric cancer cell proliferation by promoting the oxygen glycolytic pathway, and Liu et al [ 58 ] indicated that downregulation of miR-1-3p expression is involved in the growth and motility of lung cancer cells. Our results suggest that IL6ST is a target gene of miR-1-3p in CAC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1-3p, a downstream target of NEAT1, has been shown to play a facilitative role in tumors. For instance, Peng et al [ 57 ] reported that miR-1-3p affects gastric cancer cell proliferation by promoting the oxygen glycolytic pathway, and Liu et al [ 58 ] indicated that downregulation of miR-1-3p expression is involved in the growth and motility of lung cancer cells. Our results suggest that IL6ST is a target gene of miR-1-3p in CAC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, TIMELESS expression was signi cantly negatively correlated with hsa-miR-1-3p expression in LUAD tumor tissues, and high hsa-miR-1-3p expression was signi cantly associated with improved OS in LUAD. Previous reports indicate that miR-1-3p has an inhibitory role in lung cancer by targeting CELSR3 and FAM83A and modulating the viability, migration, and invasion of tumor cells [25][26][27]. According to the ceRNA hypothesis [28], lncRNAs in the lncRNA -hsa-miR-1-3p -TIMELESS interaction network in LUAD should be oncogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this interaction has been mapped at the SH3 domain of c-Src and the poly-proline region N-terminal of ChoKα [99]. The relationship of ChoKα and EGFR, has also been reported in lung [100] and liver tumors [35] and has been associated with resistance to EGFR inhibitors [35]. In prostate cancer, ChoKα acts as a chaperone for the androgen receptor (AR), elucidates a feed-forward signalling loop that maintains ChoKα expression and as a consequence reinforces AR signaling activity.…”
Section: Choks More Than Metabolism Enzymes?mentioning
confidence: 91%
“…It has been shown that miR-367-3p targets the 3'-UTR of the chka mRNA transcript with strong affinity in MCF7 breast cancer cells and, as a consequence, represses its expression [131]. In the lung cancer cell lines H1355 and A549, miR-1-3p regulates the EGFR/MAPK/ChoKα signaling pathway through modulation of the expression of FAM83A (Family with sequence similarity 83, member A) [100] a gene involved in the onset of lung adenocarcinoma [132]. These interesting findings open the possibility to explore alternative strategies for the control of ChoKα levels and activity as therapeutic approaches.…”
Section: Choks More Than Metabolism Enzymes?mentioning
confidence: 99%